Britain's persuaders : soft power in a hard world - Ramscar, Helen (London [England] : I.B. Tauris, 2021)
This book conducts an up-to-date 'audit' of all Britain's principal sources of soft power. Situating its analysis within the current understanding of the 'smart power' of nation states - that desire to employ the full spectrum of policy instruments and national characteristics to achieve policy outcomes, specifically in the context of 'Brexit Britain' where soft power status is certain to loom larger during the 2020s.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Diplomacy; Great Britain -- Foreign relations; Diplomacy; Electronic books